Artistic Expression of Russian National-Cultural Concept of River in M. Yu. Lermontov’s Works - T. B. Radbil; I. S. Yukhnova (Научный диалог, 2019)
The author’s individual artistic expression of the concept of RIVER in the artistic world of M. Yu. Lermontov is considered. The aim of the research is a complex philological (linguistic and literary) analysis of the RIVER concept in the Russian national conceptual sphere through the prism of its aesthetic transformation in M. Yu. Lermontov’s works. The materials of the research are the data of lexicographical sources - the main etymological, explanatory and special dictionaries of the Russian language, and the texts of poetic and prose works by M. Yu. Lermontov. The research is based on the method of linguocognitive analysis of culturally significant concepts in the system of language and on the method of literary analysis of “toposes” as landscape elements, acting as integral principles of the organization of the total artistic world of the author. It is shown that Lermontov’s RIVER topos as a whole correlates with the meanings that are characteristic of the corresponding concept in the Russian national language consciousness, but the greatest relevance for the artistic world of Lermontov have values associated with the idea of the border, the boundary, as well as the idea of time, the idea of life and its course, the idea of death. The practical significance of the study is that its main results can be used in the teaching of cognitive linguistics, linguoculturology, the basics of conceptual analysis, theory of literature, history of Russian literature, as well as in the practice of compiling dictionaries of a new type - dictionaries of concepts (including educational), linguistic and cultural thesauruses and literary dictionaries of “toposes” of Russian literature.